Internalization of Indigenous Knowledge in the Education Curriculum for Next Generation Science Standards (NGSS) - Parmin, Parmin; Trisnowati, Eli (LPMPP Universitas Negeri Yogyakarta, 2024)
Indigenous knowledge in Indonesia is very diverse, but some of it is threatened with extinction due to the impact of modernization on people's lifestyles. This research aims to find new methods of integrating indigenous knowledge into the curriculum for preparing prospective science teachers. The new method is targeted to become a reference for prospective science teacher education providers in Indonesia. The research uses mixed methods to find the impact of integrating indigenous knowledge in the curriculum for preparing prospective science teachers, according to the NGSS. The impact on prospective science teachers' profiles is the ability to integrate indigenous knowledge in preparing NGSS. The research targets were 15 heads of science education study programs from 15 different tertiary institutions and 20 prospective science teachers from three different study periods (one year, two years, and more than three years). The difference between study periods is considered because applying a curriculum integrating indigenous knowledge has only begun in the three classes used in this study. The research results found that the longer the study period, the more prospective teachers have the skills to integrate indigenous knowledge more clearly. The N-Gain test obtained a result of 0.5 (medium), meaning that the existing curriculum on the skills of applying science concepts to prospective science teachers about indigenous knowledge is in the medium category. Systematic integration of the curriculum for preparing prospective science teachers makes NGSS and indigenous knowledge in academic texts, courses, teaching materials, and final projects for graduation requirements.